PENDIDIKAN AGAMA BAGI LANSIA DI GRIYA WERDHA (SEBUAH PERSPEKTIF PENDIDIKAN ISLAM DAN PSIKOLOGI) - Noor, Triana Rosalina; Inayati, Isna Nurul (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2021)
Islamic education is important to be given through the cultivation of religious values from prenatal to old age. This is because in old age, it is a time when man has a developmental duty to draw closer to God. Not all elderly people spend their old time together with their families at home, but there are elderly people who have to spend the rest of their life in a griya werdha. The social services provided in griya werdha are not only physical, but also spiritual. The research method used is the study of literature, namely conducting the process of studying books, theories that exist to be related to the topic of religious soul development in the elderly. The results of this study show that through Islamic religious education, the elderly will be helped to be able to heed the feelings of helplessness and waste felt through activities that increase the spirituality that exists. This means that even in the elderly stage, the elderly can still perform their functions and roles appropriately based on their status in the situation and conditions they face.